Biosafety Measures in the Laboratory during Handling of Specimens of Suspected COVID-19 Patients (Bangladesh Journal of Infectious Diseases, 2020)
Abstract not available.Bangladesh Journal of Infectious Diseases, April 2020;7(suppl_1):S66-S68